A Case of Burnt out Diabetes in an End Stage Renal Disease Patient at a Private Multispeciality Tertiary Care Hospital - Srimathi, Sivaramakrishnan; Jacob, Juby Liz (Indian Journal of Pharmacy Practice)
Burnt-out diabetes is a state in which diabetic patients with End Stage Renal Disease (ESRD) experience hypoglycemic episodes accompanied by a normalization of Glycosylated Hemoglobin A1c (HbA1c) levels. Here we present a case of ‘burnt-out diabetes’ in a female patient who went into sudden cardiac arrest during hemodialysis. Patient reverted and after intubation was admitted under intensive care. Investigations revealed severe Chronic Renal Failure (CRF), mild concentric left ventricular hypertrophy (LVH) and mild pulmonary arterial hypertension (PAH). She was treated with intravenous antibiotics, diuretics, antihypertensives. She had four sittings of hemodialysis during her hospital stay and was later discharged and advised regular hemodialysis. In conclusion, this is a case that involves interplay of diabetes and kidney disease. This emphasizes the need to evaluate the risks associated with the overestimation of glycemic control in ESRD patients on hemodialysis and for the use of alternative indicators of glycemic control such as Glycated Albumin (GA).
Keywords: Diabetes mellitus; Glycosylated hemoglobin; Hemodialysis; Glycemic control; Glycated albumin.